Pressure-Driven Flow of Cross Fluid Along a Stationary Plate Subject to Binary Chemical Reaction and Arrhenius Activation Energy - Mustafa, M.; Sultan, Aiman; Rahi, Mahmood (Arabian journal for science and engineering (2011), 2019)
The present paper deals with the flow of Cross rheological fluid along a stationary rigid plate caused by stream-wise pressure gradient. Flow field is affected by uniform magnetic field acting normal to the plate axis. Interaction of flow field with chemically reacting solute is modeled through the advection–diffusion equation in which temperature dependency of the reaction rate on activation energy is considered. Energy equation containing source term and variable thermal conductivity is treated. Locally similar solutions are obtained and interpreted for a certain range of embedded parameters. Shear-thinning aspect of Cross fluid is apparent from the computational results. A monotonic decay in vertical velocity is noticed for increasing values of flow behavior index ( n ) which, in turn, leads to pronounced heat conduction. An important finding is that activation energy of chemical reaction remarkably alters the solute concentration near the plate.